Jewish messianic thoughts in an age of despair - Seeskin, Kenneth, 1947- (Cambridge ; New York : Cambridge University Press, 2012)
"This book asks whether hope for a better future is defensible in light of the human propensity for evil"--
Machine generated contents note: 1. Messianism and mythology -- 2. Maimonedes and the idea of a deflationary Messiah -- 3. Internalism: the Messiah within -- 4. Infinite deferral -- 5. History and rationality -- 6. History and irrationality -- 7. Redemption.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Messiah -- Judaism; Redemption -- Judaism; Despair -- Religious aspects -- Judaism; RELIGION / Judaism / General; RELIGION / Judaism / Theology; Electronic books